The Effect of Product Quality on Purchasing Decisions with Customer Reviews and Ratings as Intervening Variables - Arsita, Herlin; Suhardi, Suhardi; Firdaus, Rahmad; Kurniadi, Dedi (Economic: Journal Economic and Business, 2025)
This study seeks to investigate the impact of Product Quality on Consumer Purchase Choice, utilising Customer Reviews and Ratings as mediating variables. The methodology used in this study is Partial Least Squares-Structural Equation Modelling (PLS-SEM) facilitated by SmartPLS software. Data was collected from 228 participants who had experience in online shopping. The research findings revealed that Product Quality exerted a positive and significant influence on Customer Reviews and Ratings, as well as on Purchase Decision. In addition, Customer Reviews and Ratings were found to positively influence Purchase Decision, albeit to a lesser magnitude compared to Product Quality. These results underscore the idea that Product Quality is an important determinant of Purchase Decision, while Reviews and Customer Ratings serve as additional factors that can enhance the decision. The implications derived from this study suggest that organisations should prioritise improving product quality as a fundamental strategy, while also managing customer reviews and ratings to increase favourable perceptions of their products.